2018
DOI: 10.3390/ijerph15112478
|View full text |Cite
|
Sign up to set email alerts
|

Income Changes Due to Disability Ratings and Participation in Economic Activities Caused by Industrial Accidents: A Population-Based Study of Data from the Fourth Panel Study of Workers’ Compensation Insurance (PSWCI)

Abstract: Industrial accidents cost a huge amount of money, but they also have negative consequences in many respects. We analyzed the data of the first to fourth panel study of workers’ compensation insurance (PSWCI). Repeated measures ANOVA was used to compare the annual income before and after the industrial accident, and a general linear model was used to identify changes in income due to disability ratings and participation in economic activities. The wages before the industrial accident and the annual income varie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
35
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(38 citation statements)
references
References 28 publications
(27 reference statements)
2
35
1
Order By: Relevance
“…The first panel study was conducted in 2013 and has since been conducted annually. Accordingly, the fifth study obtained survey data during 2017, using a computer-assisted personal interviewing (CAPI) method together with face-to-face interviews conducted by skilled interviewers [2,3,22,23,27,28,29,30]. The fifth survey included 1616 workers who had participated since the first survey, yielding a retention rate of 80%.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The first panel study was conducted in 2013 and has since been conducted annually. Accordingly, the fifth study obtained survey data during 2017, using a computer-assisted personal interviewing (CAPI) method together with face-to-face interviews conducted by skilled interviewers [2,3,22,23,27,28,29,30]. The fifth survey included 1616 workers who had participated since the first survey, yielding a retention rate of 80%.…”
Section: Methodsmentioning
confidence: 99%
“…Although the number of Korean workers involved in industrial accidents has declined steadily from 2008 to 2017, the annual number of reported cases continues to exceed 90,000 [1,2,3]. Industrial accidents have various negative consequences, including high social costs and loss of productivity in the workplace [3,4,5,6]. The injured workers also face issues associated with recovery and loss of income [7,8,9].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations